2018 17th IEEE International Conference on Trust, Security and Privacy in Computing and Communications/ 12th IEEE International 2018
DOI: 10.1109/trustcom/bigdatase.2018.00250
|View full text |Cite
|
Sign up to set email alerts
|

Towards Malware Detection via CPU Power Consumption: Data Collection Design and Analytics

Abstract: This paper presents an experimental design and data analytics approach aimed at power-based malware detection on general-purpose computers. Leveraging the fact that malware executions must consume power, we explore the postulate that malware can be accurately detected via power data analytics. Our experimental design and implementation allow for programmatic collection of CPU power profiles for fixed tasks during uninfected and infected states using five different rootkits. To characterize the power consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
(44 reference statements)
0
15
0
Order By: Relevance
“…A typical example of the use of energy-based mechanisms is [113], which experimentally confirms that many rootkits change the CPU power profile. This trait can be used to detect the attack via specific time series-based algorithms.…”
Section: Energy-based Methodsmentioning
confidence: 68%
“…A typical example of the use of energy-based mechanisms is [113], which experimentally confirms that many rootkits change the CPU power profile. This trait can be used to detect the attack via specific time series-based algorithms.…”
Section: Energy-based Methodsmentioning
confidence: 68%
“…[37] described a network time analysis approach for monitoring performance changes caused by hardware virtualization, with the goal of detecting the hardware virtualization rootkit. [11,39] identify rootkits by using power-based malware detection on general-purpose computers and [19,39,61] use machine learning (ML) and deep learning (DL) to perform a behavioral detection method based on CPU power consumption. Gibraltar [6] and Copilot [49] leverage direct memory access (DMA) via physical PCI to separately detect rootkit in kernel memory from another machine.…”
Section: Related Workmentioning
confidence: 99%
“…Bridges et al [43] have shown that profiling of device power is a viable approach. They found that by directly monitoring the power usage of a CPU that an accurate power profile could be constructed.…”
Section: Device Profilingmentioning
confidence: 99%